Transcriptome Analysis of Multiple Metabolic Tissues in High-Salt Diet–Fed Mice - Fei Mao; E. Wang; Jing Xu; Jin Lu; Guofeng Yan; Li Fu; Yang Jiao; Ling Wu; Tiemin Liu; Yao Li (Frontiers in Endocrinology, 2022)
High-salt diet (HSD) is associated with dysregulated metabolism and metabolic disorders. Although previous studies have indicated its effect on metabolic tissues, the involving molecular mechanisms are not quite understood. In the present study, we provided a comprehensive transcriptome analysis on multiple metabolic tissues of HSD-fed mouse model by RNA sequencing. We observed that several genes associated with de novo lipogenesis and cholesterol biosynthesis were significantly downregulated in white adipose tissue and liver tissue of HSD mice group, such as Fasn, Scd1, Acaca, and Thrsp. Furthermore, combined with secretome datasets, our results further demonstrated that HSD could alter expression levels of organokines in metabolic tissues, for example, Tsk and Manf, in liver tissue and, thus, possibly mediate cross-talk between different metabolic tissues. Our study provided new insight about molecular signatures of HSD on multiple metabolic tissues.